Visual neuroprostheses: history, contemporary state, development perspectives - Tsymbalyuk, V.; Parpaley, Y. (Ukrainian Neurosurgical Journal)
Significant prevalence of blindness and reduction in quality of blind people’s life is conditioned urgency of researches in sight restorations techniques. The concept of using of safe structures in vision system at irreversible blindness for electrical stimulation and producing of visual prosthesis is not new one. Despite of the efforts of neurophysiologians, doctors and engineers creation of useful visual prosthesis remains till now only prospect. The history of creation, modern development of retinal and cortical vision prostheses, problems and also prospects of their decision in the future are submitted.